A correlation study of cytopathology and histopathology and the associated risk for malignancy thyroid nodule - Ghazali, Mohd Firdaus (2017)
Introduction: Thyroid nodule incidence has been reported increasing worldwide due to various factors. In order to determine the management of this entity, Fine needle aspiration cytology (FNAC) and histopathology examination must be performed to correctly identify the tissue diagnosis. Approximately 10-20% of thyroid FNAC diagnoses fell into Bethesda III & IV category and carried 5-30% risk of malignancy. We aim to identify the occurrence and clinical predictors towards malignancy in these groups. Objective: The main objective is to study the agreement between cytopathology and histopathology in thyroidectomy patients and to identify the associated risks of malignancy in patients with Bethesda III & IV thyroid nodule. Methods: Patients who underwent thyroidectomy with prior FNAC between June 2007 and May 2013 in Hospital Raja Perempuan Zainab II, Kota Bharu, Kelantan were retrospectively reviewed demographically. Final histopathology were analyzed and compared. The specificity and sensitivity study of thyroid FNAC were calculated and recorded. The associated risk for malignancy in indeterminate cytology nodule including age, gender, race, thyroid status, duration, symptomatic nodule and nodularity were reviewed. Results: A total of 333 patients (mean age ± SD, 44.07 ± 14.3 years) were enrolled with gender ratio of 1:4 (male to female), and majority of patients were Malay ethnic (94.6%). Mean duration of thyroid nodule was 4.72 years (SD = 6.007). The correlation between cytopathology and histopathology has substantial strength of agreement (Cohen’s Kappa analysis, ĸ= 0.751 (95% CI: 0.671, 0.831). The sensitivity, specificity, positive predictive value, negative predictive value, false positive rate, false negative rate and total accuracy of FNAC were 89%, 91%, 76%, 96%, 9%, 11% and 90%, respectively. Commonest malignancy detected was papillary thyroid carcinoma in 60 patients (74.1%). In patients with cytology Bethesda III & IV, the presence of multiple nodule (58% vs. 42%, p=0.036) was associated with higher malignancy risk. Neither age, gender, race, thyroid status, duration nor symptomatic nodule were associated with malignancy risk. Conclusion: Thyroid nodule is predicted higher incidence and FNAC is gold standard preoperative procedure with high accuracy. In patients with Bethesda III & IV cytopathology, we noted the presence of multiple nodules was associated with increased risk for malignancy.